Effect of parathyroidectomy on quality of life and non-specific symptoms in normocalcaemic primary hyperparathyroidism. Issue 3 (5th February 2018) - Bannani, S; Christou, N; Guérin, C; Hamy, A; Sebag, F; Mathonnet, M; Guillot, P; Caillard, C; Blanchard, C; Mirallié, E
Abstract: Background: Normocalcaemic primary hyperparathyroidism (NcPHPT) is a new clinical entity being diagnosed increasingly among patients with mild primary hyperparathyroidism (PHPT). The aim of this study was to evaluate quality of life and non-specific symptoms before and after parathyroidectomy in patients with NcPHPT compared with those with hypercalcaemic mild PHPT (Hc-m-PHPT). Methods: This was a prospective multicentre study of patients with mild PHPT from four university hospitals. Patients were evaluated before operation, and 3, 6 and 12 months after surgery for quality of life using the SF-36-v2® questionnaire, as well as for 25 non-specific symptoms. Results: Before operation, the only statistically significant difference between the NcPHPT and Hc-m-PHPT groups was in the mean(s.d.) blood calcium level (2·54 versus 2·73 mmol; P < 0·001). At 1 year after surgery, the blood calcium level had improved significantly in both groups, with no significant difference between them. Quality of life improved significantly in each group compared with its preoperative score, with regard to the physical component summary ( P = 0·040 and P = 0·016 respectively), whereas the mental component summary improved significantly in the Hc-m-PHPT group only ( P = 0·043). Only two non-specific symptoms improved significantly in the NcPHPT group compared with nine in the Hc-m-PHPT group. Conclusion: Parathyroidectomy mildly improves quality of life and some non-specific symptoms in patients with NcPHPT. Abstract : Little improvement